Research on Combustion Chamber Structure Improvement and Ignition System of Missile Turbojet Engine for Diesel Fuel - Lei Qiu; Xi Zeng; Shiming Ji; Fengfei Xi; Wenbin Qiu; Qianqian Zheng (Tehnički Vjesnik, 2018)
To meet the conditions of diesel ignition, this paper presents several structural improvements of a small missile turbojet engine for diesel fuel. The engine starts motor-assisted, and its fuel is ignited by silicon nitride ceramic ignitor. Theoretical analysis is performed by establishing a mathematical model of the combustion model and combustion conditions. The feasibility of diesel used as a small turbojet fuel is analyzed by using numerical simulation software. Research is carried out based on the following points: the improvement of combustion chamber and evaporator, selection of ignitor position and sustainability of fire. This paper proposed the method of linking the engine-assisting startup system and selected the right type of ignitor, and on the advanced experimental platform several groups ignition tests were carried out.